Economics of the Arab awakening: From revolution to transformation and food security - Breisinger, Clemens; Ecker, Olivier; Al-Riffai, Perrihan (International Food Policy Research Institute, 2011)
Few observers would have predicted the dramatic changes over the past few months in the Arab world. Arab governments appeared to be in tight control, and many Arab economies were growing around or above the world average over the past few years. Annual growth rates in Egypt, Jordan, Lebanon, Oman, and Sudan averaged more than 6 percent between 2005 and 2010; and Syria, Tunisia, and Libya grew at about 5 percent on average during the same period of time. Official poverty rates in most Arab countries are lower than in many Asian and Latin American countries. However, experts have long identified slow progress in economic diversification and job creation, social inequalities, and persistent food insecurity as major development challenges for Arab countries. Did these factors and, more broadly, people's dissatisfaction with their living standards contribute to the recent uprisings? At first glance, the sudden turn of events and the generally low coverage, quality, and accessibility of data in the Arab world make it difficult to find answers to this question. By looking beyond more conventional data, however, this policy brief provides some insights into the potential role of economics in the ongoing uprisings. It also reviews major policy responses of Arab governments and provides a new narrative of Arab development that is based on inclusive economic transformation, food security, and decisionmaking.